Social phobia among long-term internally displaced persons: An epidemiological study of adults in two internally displaced person settlements in Sudan. (September 2015) - Salah, Tarig Taha Mohamed; Ayazi, Touraj; Lien, Lars; Eide, Arne; Hauff, Edvard
Background: Despite the high worldwide prevalence and association with other mental disorders and disability, only few studies are available on social phobia in low-income countries. Aims: This study aims to assess the prevalence, socio-demographic correlates and comorbidity of social phobia and its association with disability among long-term internally displaced persons (IDPs) in one urban and one rural area in Central Sudan. Methods: This cross-sectional study was implemented in two IDP areas in Central Sudan. Data were collected during face-to-face interviews using structured questionnaires to assess socio-demographic factors and the Mini International Neuropsychiatric Interview (MINI) to determine psychiatric diagnoses. A total of 1, 876 adults were enrolled from both study areas. Results: The overall lifetime prevalence of social phobia was 14.2%, with higher rates among IDPs in the rural area and among those who were less educated. Social phobia was associated with other mental disorders in both study areas. Disability and prolonged displacement increased the risk of having social phobia in the rural area. Conclusion: Further work needs to be done to improve our understanding and to establish proper interventions in dealing with social phobia, other common mental disorders and disability among long-term IDPs in these impoverished areas.